DIGITALIZATION: IMPROVING THE LITERACY OF FOREIGN LANGUAGE LEARNERS THROUGH MULTIMODAL TEXTS - Afifah, Lilis; Indriwardhani, Sri Prameswari; Retnantiti, Sawitri; Usman, Rizman (Lire Journal (Journal of Linguistics and Literature), 2023)
The development of teaching materials is one of the most important elements that can support the quality of the learning process, including foreign language learning. In contrast to technological developments, teaching materials for Arbeit am Text courses studied by students at Universitas Negeri Malang (UM) are still conventional and have not received sufficient attention for a long time. On the other hand, the course that focuses on German reading skills has an important goal, namely, to improve student literacy. Therefore, this study aims to develop multimodal-based teaching materials for Arbeit am Text courses. In this research and development, researchers used the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). Questionnaire sheets were delivered to the material expert as well as to the media expert to earn product validity. Besides, e-questionnaires were also filled out by students as users of the teaching materials arranged. Based on the data validation results, it can be concluded that the multimodal-based digital teaching materials for the Arbeit am Text course were declared to meet the eligibility requirements for media and material with respective percentages of 94% and 95.28% so they are included in the "very good" category. Likewise, the results of trials on users, namely students who took part in the lectures, had given very positive responses to the multimodal-based digital teaching materials designed by researchers. Researchers hope that multimodal-based digital teaching materials can be used widely, especially in learning the Arbeit am Text course, and can be used as a source of independent learning outside the lecture process.